Training Primary Care Physicians for Local Health Authority Duties in Texas - Mobley, James (American Public Health Association, 2012)
Only one fourth of Texas counties have a local health authority (LHA) or health district. Primary care physicians in the remaining counties could be trained in public health basics by providing an online LHA training course and courses at annual meetings of the Texas Medical Association and the Texas Academy of Family Physicians. The Texas Department of State Health Services should develop a web portal for LHAs. The Texas Association of Local Health Officials should also provide automatic limited membership for LHAs. These initiatives would provide public health training to primary care physicians and would greatly improve availability of public health services for the citizens of Texas.